Role of Online Community Feedback in Creating the Image of Tourist Destinations - Muhammad Muzamil Sattar; Fabiola Sfodera (ASEAN Journal on Hospitality and Tourism, 2023)
This study investigates the impact of user generated content on online platforms, mainly known as Online Community Feedback (OCF). This study aims to highlight the importance of OCF in developing destination image. Content and feedback given by past visitors are more trustworthy as compare to any other information sources including advertisements by site managers or information from government ministries. Based on this phenomena authors of this paper have categorized and analyzed the feedback and comments of past tourist of Gilgit Baltistan Region of Pakistan. Authors have adopted unstructured approach and manual approach to categorize the feedback into different parameters. Based on those, several recommendations are made to government officials and tourist site managers to bring improvements on the site so that future tourists may choose that place for their next visit. Top 5 places of Pakistan as per tripadvisor.com, were chosen for analysis and study.